The Effectiveness of Tuberculosis Control Program in Rural Area, Indonesia - Tamrin, Kiswah (Postgraduate Program in Public Health, Universitas Muslim Indonesia, 2022)
Background: Pulmonary tuberculosis (TB) is a contagious infectious disease caused by the Bacterium Mycobacterium Tuberculosis, which can attack various organs, especially the lungs. Since 1995, Indonesia has implemented a program to eradicate pulmonary TB through pulmonary TB treatment with the DOTS (Directly Observed Treatment Short-course) strategy that can break the chain of transmission of the disease. The high number of pulmonary tuberculosis patients in the working area of ​​the Mattombong Health Center is inseparable from the participation of the government, health workers, facilities, and infrastructure, as well as the participation of the community which lacks synergy in the discovery and treatment of pulmonary TB disease. Lack of synergy seems to be a condition where public awareness is not yet high, in order to carry out regular and disciplined treatment, while on the other hand monitoring and evaluation of health workers is still lacking. This study aims to describe the effectiveness of Tb control program in rural area, Indonesia. Methods: This is a qualitative study. The data collection method was done by in-depth interviews and observations. Informants in this study consisted of chief program at the Deli Serdang District Health Office, Head of primary healthcare center (puskesmas), Pulmonary TB Officers, Laboratory Officers, Pharmacy Officers, Pulmonary TB Patients, and Drug Swallowing Supervisors (PMO). Results: The implementation of the pulmonary TB control program had not been effective because the patient's recovery rate in 2021 was still 25%. This figure is still far from the target for the success rate of treatment or cure for pulmonary TB nationally, which is 85%. Conclusions and suggestions: Based on the results of the research, it is hoped that the Pinrang District Health Office will continue to actively carry out supervision and monitoring of the implementation of the DOTS Strategy in the working area of ​​the Puskesmas. besides evaluating and solving problems in TB disease management.